Sistem Pendukung Keputusan Aplikasi Rental Mobil Menggunakan Metode SAW (Simple Additive Weighting) - Charles, Charles; Jessica; Irwansyah, Joni; Oktovia , Sendy (Journal of Digital Ecosystem for Natural Sustainability, 2024)
Batam, a strategic city in Indonesia's Riau Islands Province near Singapore and Malaysia, is a hub of economic activity, trade, and tourism, resulting in high mobility demands. The increasing need for transportation services, including car rentals, highlights the importance of efficient and practical solutions to support daily activities and business operations. To address growing demand, car rental companies in Batam have adopted Decision Support Systems (DSS) to enhance service quality. DSS helps analyze data and provides recommendations, enabling customers to select vehicles that meet their needs. One method implemented in DSS is the Simple Additive Weighting (SAW) technique, which evaluates criteria such as price, vehicle type, capacity, and comfort. SAW ensures systematic, transparent decision-making, reducing bias and enhancing customer satisfaction. By integrating SAW, car rental businesses in Batam improve operational efficiency, offer competitive services, and meet customer expectations in a rapidly growing market.